PENERAPAN MODEL DISCOVERY LEARNING (DL) DALAM PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR (STUDI LITERATUR) - Mitra, Yulia; Taufik, Taufina (Universitas Negeri Padang, 2022)
This study aims to re-analyze the use of discovery learning models in integrated thematic learning in elementary schools. The design of this study is Literature Review. A literature review study is a method used to collect data or sources related to a particular topic that can be obtained from various sources such as journals, books, internet, and other literature. The purpose of this study is to describe the application of the Discovery Learning (DL) model to integrated thematic learning in elementary schools. Data collection is done by using non-test that is by searching electronic journals through Google Scholar and study documentation in the library. From the research results 15 relevant articles show that the Discovery Learning model is effective in improving student learning outcomes. The key word used for journal research is Discovery Learning, integrated thematic. In this study, researchers used a literature study, first the researchers formulated the research problem, then proceeded to explore existing research relevant to analysis. From the research results 15 relevant articles show that the Discovery Learning (DL) learning model is effective in improving student learning outcomes.